Deradikalisasi Narapidana Teroris dalam Lembaga Pemasyarakatan - Subki, Ahmad Ibnu; Fathinnuddin, Muhammad (HUMANIORUM, 2024)
Deradicalization of terrorist prisoners in correctional institutions is a strategic step in efforts to prevent future acts of terrorism. This program aims to change the mindset and behavior of prisoners so that they are no longer influenced by radical ideology. The success of deradicalization is highly dependent on the synergy between the government, law enforcement officers, and the community in creating an environment that supports the social reintegration of former prisoners.This study uses a qualitative approach with literature study methods and interviews with stakeholders involved in the deradicalization program. The data collected were analyzed descriptively to identify supporting factors and challenges in implementing this program.The results of the study indicate that the effectiveness of deradicalization is influenced by internal factors, such as the level of individual acceptance of the program, as well as external factors, such as social support and correctional policies. Although there are challenges, such as limited resources and prisoner resistance, a multidisciplinary approach that includes religious, psychological, and economic aspects has been shown to increase the effectiveness of the program. Therefore, evaluation and strengthening of deradicalization policies are needed so that this program can run optimally and sustainably.